Synthesis, Characterization and Kinetics of N,N'-Ethane Bridged Copper(II) Complex with ct-DNA - Ahmad Tak, Aijaz; Qayoom, Taulat; Shameem, S.A.; Akram, S.M.M. (Asian Journal of Chemistry, 2010)
Novel N,N'-ethane bridged complexes of copper(II) were prepared, which can act as potential drug. Structural elucidation of the complexes was performed on the basis of elemental analysis, IR, UV-vis, EPR, conductance measurements and NMR spectroscopy. All the spectroscopic data indicate ionic nature and square planar geometry for the metal ion. Kinetic studies were carried out with ct-DNA to ascertain the metal DNA interaction by spectrophotometric method at lmax (446 nm) of Cu(II) complex at 30 ± 1 ºC. On interaction with ct-DNA, the absorption spectra exhibits a shift in wavelength and steep decrease in the absorbance, indicates the binding of ct-DNA with Cu(II) complex. The rate constants were calculated under pseudo-first order conditions and the plot of Kobs versus [DNA] give a straight line. The electrochemistry of ct- DNA-metal binding was carried out in H2O/DMSO (95:5). The shift in formal potential after interaction with ct-DNA evidences the binding of Cu(II) complex to the ct-DNA. The ratio of anodic to cathodic peak currents Ipa/Ipc for free Cu(II) complex is 0.8 while for the DNA bound metal complex the ratio decrease to 0.5, suggesting that ct-DNA is bound strongly to the complex.